Transitioning EPMA applications in a large multisite teaching hospital. Issue 4 (18th November 2022) - Silva, Geeth; Hall, Graeme; Vogel, Aaron; Bourne, Tim; Xu, Gang
Abstract : Introduction: University Hospitals of Leicester (UHL) has co-developed and deployed a novel Electronic Prescribing and Medicines Administration (EPMA) application as part of the trust electronic patient record (EPR) programme that meets specific clinical demands and interoperability standards of the National Health Service (NHS) despite clinical pressures from the COVID-19 pandemic. Methods: Following an initial limited pilot deployment, a big-bang whole site-based approach allowed transition of 1844 acute adult inpatients beds from an existing standalone EMPA to the new system. This project used a frontline driven and agile management strategy. Clinical risk was managed using a combination of standard risk logs, robust clinical prototyping and robust disaster recovery plans. Early engagement with clinical teams allowed for advanced product configuration before live deployment and reduced the need for sustained transition support for clinical staff. Results: An iterative, well-governed approach, led by a combination of information technology (IT) and clinical staff with a responsive vendor, enabled a complex new EPMA system in a large acute NHS trust to be deployed with limited resources despite the ongoing COVID-19 pandemic. Discussion: The development and deployment of EMPA and EPR systems across NHS trusts is a key enabler for better healthcare delivery. This case study shows it is possible to deploy a new clinical IT system at scale without interruption of clinical services and with a relatively modest deployment team. Sustainability of the project was also ensured through a clear clinically led governance structure to manage risk quickly and carry lessons learnt onto new developments.